Mitochondria and Cytoskeleton rearrangement in Drp1 overexpressing skeletal muscle - Giovarelli, Matteo; Zecchini, Silvia; Moscheni, Claudia; Procacci, Patrizia; Sartori, Patrizia; De Palma, Clara (Italian Journal of Anatomy and Embryology, 2018)
In skeletal muscle mitochondrial fusion and fission define the mitochondrial network mor- phology regulating myofiber differentiation, muscle contraction and the response to stress conditions 1-3. Mitochondrial fission is mainly mediated by dynamin-related protein 1 (Drp1) which represents a critical player in myogenesis and its inhibition suppresses myotube forma- tion 4-5.Our work is focused on a transgenic mouse overexpressing Drp1 specifically in skel- etal muscle (Drp/MC). Drp/MC mice show growth defects starting from P7 mainly due to an impairment of glycolytic muscles development; indeed, in adult phase they display an over- all 20% reduction of body weight and a drop of locomotor performance without any increas- ing in catabolic processes. Drp/MC mice exhibit low mitochondrial DNA levels which trigger mitochondrial stress and upregulate the unfolding proteins response (mtUPR) together with an impairment of Growth Hormone anabolic pathway. Interestingly, we observe a strong remod- eling of mitochondria distribution with a depletion of inter-myofibrillar mitochondria and an enrichment of the sub-sarcolemmal pool. In parallel, we observe a perturbation of cytoskeleton framework characterized by the disruption of Desmin network (the main skeletal muscle inter- mediate filament connecting mitochondria to cytoskeleton) with the presence of Desmin aggre- gates inside myofibers and its accumulation beneath the sarcolemma. Moreover, in vivo time- lapse imaging of both skeletal muscle fibers and satellite cells-derived myotubes, indicates an increased mitochondrial mobility in Drp/MC mice; therefore, our aim is the evaluation of the role of different motor proteins, such as the kinesin (Kif5b and KLC1) and dynein, in the Drp/ MC dysregulated muscular and mitochondrial phenotype.